Numerical Simulation of Dry and Wet Rice Seeds in an Air-Suction Seed Metering Device - Cheng Qian; Zhuorong Fan; Daoqing Yan; Wei Qin; Youcong Jiang; Zishun Huang; He Xing; Zaiman Wang; Ying Zang (Agronomy)
Rice direct seeding for bunch planting is a sustainable agricultural production method that reduces production costs, improves rice lodging resistance, and conserves irrigation water in the field. However, there are notable differences in seed treatment between direct seeding on dry land and in paddy fields, which can impact the seeding process’s accuracy. This study employs the numerical simulation methods of computational fluid dynamics (CFDs) and discrete element method (DEM) to examine the motion characteristics of dry and wet rice seeds in a fluid–solid coupled domain and their impact on seeding accuracy. The aim is to guide the optimization of the rice air-suction seed metering device. Rice seeds were divided into dry and wet groups, and their physical properties were measured. Discrete element models of rice seeds were constructed and calibrated using a polyhedral method. The results show that the static friction coefficient between the seed meter and the seed ranged from 0.902 to 0.950, and the thousand-grain weights ranged from 25.89 to 32.42 g, which were higher than those of the dry rice seed, which ranged from 0.774 to 0.839, and from 25.89 to 32.42 g. After calibration, the errors between the simulated dynamic stacking angles of HHZD, HYD, YLYD, HHZW, HYW, and YLYW and the physical–dynamic stacking angles were 0.12%, 0.13%, 0.75%, 0.62%, 0.08%, 0.75%, 0.59%, and 1.24%, respectively, which indicated that the discrete element model for rice was reliable. Additionally, a seeding accuracy test revealed that wet seeds of the same variety had higher missing and single indices, while dry seeds had higher triple and multiple indices. Furthermore, CFD-DEM simulations demonstrated that wet seeds’ normal and tangential forces were more significant than those on dry seeds during the seed-filling process. At 40 rpm, the normal and tangential forces during the seed-filling process of HYW are 37.69 × 10−3 N and 12.47 × 10−3 N, respectively, which are higher than those of HYD (25.18 × 10−3 N and 9.19 × 10−3 N). The action force of suctioned rice seeds was directly proportional to the missing and single indices. The primary factors contributing to the discrepancy in seeding accuracy between dry and wet rice are the thousand-grain weight, the static friction coefficient between the seed meter and the seed, and the action force exerted between the rice seeds. In addition, using a shaped hole structure and optimizing the seed chamber structure can reduce normal and tangential forces and improve seeding accuracy. This study provides a reference for the simulation of rice seed flow-solid coupling and optimization of air-suction seed metering devices.